Synthesis of spiroindolenines through a one-pot multistep process mediated by visible light - Gambuti, Francesco; Pizzorno, Jacopo; Lambruschini, Chiara; Riva, Renata; Moni, Lisa (Beilstein Journal of Organic Chemistry, 2024)
Spiro-heterocyclic indolenines are privileged scaffolds widely present in numerous indole alkaloids. Here, we develop a novel approach for the one-pot multistep synthesis of different spiro[indole-isoquinolines]. The protocol proposed involves the visible light mediated oxidation of N-aryl tertiary amines using bromochloroform with the generation of a reactive iminium species, which reacts with an isocyanide and an electron-rich aniline in a three-component Ugi-type reaction to give an α-aminoamidine. This compound might undergo an additional visible light-mediated oxidation to furnish a second iminium intermediate, which acts as electrophile in an intramolecular electrophilic aromatic substitution giving the final spiro-indolenine. The scope of the process has been investigated with respect to all three components. Simple operations, mild conditions, and good yields make this strategy a convenient and sustainable way to obtain novel spiro-indolenine derivatives.
Keywords: isocyanide; multicomponent reactions; one-pot reaction; oxidation; spiroindolenine; Ugi reaction; visible light